Approximation Properties by $q$-Durrmeyer-Stancu Operators (Analysis in Theory and Applications, 2013)
In this paper, we are dealing with $q$-Bernstein-Durrmeyer-Stancu operators. Firstly, we have estimated moments of these operators. Then we have discussed some approximation properties and asymptotic formulas. We have obtained better estimations by using King type approach and given statistical convergence for the operators.
Keywords: $q$-Durrmeyer operator; $q$-Jackson integral; $q$-Beta function.